Comunidades vegetales rupícolas y subrupícolas del sudeste ibérico (Sierra de Los Filabres) - Cabello, Javier; Valle Tendero, Francisco; Mota, Juan F. (Lazaroa, 2001)
The Los Filabres mountain range is an interesting biogeographic territory, where clear environmental contrasts exist, with many ecological gradients. After territorial stratification, we identified the various rupicolous and subrupicolous habitats where the plant communities were sampled using the classical phytosociological method. Eleven phytocoenoses were found beloging to five phytosociological classes, in which Teucrio-Kerneretum boissieri subas. alyssetosum cadevaliani, Cosentinio-Teucrietum freynii or Centrantho nevadensis-Sedetum brevifolii stand out. A new community of Saxifraga trabutiana and a new association Diantho broteroi-Launaetum laniferae are also described.